Efficacy of combination antibiotic therapy including inhaled tobramycin on Burkholderia cepacia pneumonia in a non-cystic fibrosis patient - Yasuhito Suzuki; Tomoyoshi Lee; Ryuichi Togawa; Riko Sato; Ryuki Yamada; Hikaru Tomita; Natsumi Watanabe; Takaya Kawamata; Mami Rikimaru; Julia Morimoto; Yuki Sato; Hiroyuki Minemura; et al. (IDCases)
Burkholderia cepacia complex (BCC) has been recognized as a serious cause of pneumonia in patients with cystic fibrosis. BCC infection has also been reported in non-cystic fibrosis patients. Notably, the mortality rate of bacterial pneumonia caused by BCC is high. Nonetheless, therapeutic management of BCC infection remains to be established. Recent reports have indicated successful treatment of BCC pneumonia with combination antibiotic therapy. However, no reports have detailed the efficacy of combination antibiotic therapy for both initial and recurrent BCC pneumonia management. We herein describe a rare case of BCC pneumonia in a non-cystic fibrosis patient that was successfully treated with a combination of intravenous, inhalational and oral antibiotics. Furthermore, antibiotic therapy including inhaled tobramycin has been continued after discharge from hospital, and no side effects or recurrence of bacterial pneumonia has been observed, although BCC has been detected in sputum. The findings of the present case suggest that combination antibiotic therapy including inhaled tobramycin may be effective for recurrent bacterial pneumonia caused by BCC. In the management of BCC infection, early diagnosis should be made based on sputum culture results, and combination antibiotic therapy should be initiated promptly.